2021
DOI: 10.3390/ijerph18030864
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Wellbeing in Physical Education and School Sports: A Systematic Review

Abstract: Mental health in children and adolescents has become an increasingly important topic in recent years. It is against this backdrop that physical education and school sports play an important role in promoting psychological wellbeing. The aim of this review was to analyse interventions for improving psychological wellbeing in this area. To this end, a literature review was conducted using four databases (WOS, SPORTDiscus, SCOPUS and ERIC) and the following keywords: psychological wellbeing, physical education, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 52 publications
0
25
0
3
Order By: Relevance
“…Also, in a systematic review by Hendriks et al (2018), they found that 78.2% of the studies were conducted in Western countries, these being conducted in general highly industrialized countries with highly educated and high‐income populations. Likewise, it has been seen that in general this type of intervention is aimed at the secondary school population (Piñeiro‐Cossio et al, 2021) but interventions are reported at both primary and secondary levels. Also, the literature indicates that interventions aimed at promoting well‐being in the school population present a great variety in terms of duration and the strategies used, reporting, for example, durations ranging from 4 to 30 weeks and reporting from 6 to 18 sessions (Tejada‐Gallardo et al, 2020).…”
Section: Interventions To Promote Subjective Well‐being In the School...mentioning
confidence: 99%
“…Also, in a systematic review by Hendriks et al (2018), they found that 78.2% of the studies were conducted in Western countries, these being conducted in general highly industrialized countries with highly educated and high‐income populations. Likewise, it has been seen that in general this type of intervention is aimed at the secondary school population (Piñeiro‐Cossio et al, 2021) but interventions are reported at both primary and secondary levels. Also, the literature indicates that interventions aimed at promoting well‐being in the school population present a great variety in terms of duration and the strategies used, reporting, for example, durations ranging from 4 to 30 weeks and reporting from 6 to 18 sessions (Tejada‐Gallardo et al, 2020).…”
Section: Interventions To Promote Subjective Well‐being In the School...mentioning
confidence: 99%
“…Similarly, sport participation may have benefits that are unique when compared to other forms of recreational physical activity [ 33 ]. However, limited conclusive evidence examining the contributions of different types of physical activity to wellbeing among adolescents is available [ 34 ], particularly in the context of NZ. Mixed findings from recent research concerning sport and wellbeing in NZ indicate that further investigation to better understand this relationship is warranted [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also experiment a greater sense of ability and efficiency to perform the tasks and exercises, as well as a feeling of being related and belonging to a group. The literature has made clear the relevance of the satisfaction of basic psychological needs in the physical and psychological health of physical education students ( Vasconcellos et al, 2019 ; Piñeiro-Cossio et al, 2021 ), so it is essential for the teacher to ensure that their students have legitimate perceptions of the corrective feedback granted.…”
Section: Discussionmentioning
confidence: 99%